Пошуковий етап педагогічного експерименту формування професійних базових компетенцій бакалаврів з психології у процесі вивчення природничо-наукових дисциплін - Хавіна, Ірина Валер'ївна (НТУ "ХПІ", 2018)
У статті розглядається пошуковий етап педагогічного експерименту формування професійних базових компетенцій у бакалаврів з психології при вивченні природничо-наукових дисциплін. Описано методики проведення експериментального дослідження. Представлені результати проведеного дослідження у пошуковому етапі педагогічного експерименту.

The article deals with the search stage of the pedagogical experiment of forming professional basic competencies in bachelors with psychology in the study of natural science disciplines. The methods of carrying out the experimental study are described. The results of the conducted research methods in the search stage of the pedagogical experiment are presented.
The search stage of the pedagogical experiment of the formation of professional basic competencies in bachelors with psychology in the study of natural science disciplines
Keywords: експеримент педагогічний; технології педагогічні; уміння; навички; здібності; competences; bachelors; psychology; natural science disciplines